Sharia Cooperative Entrepreneurship Development Model in Improving the Performance and Competitiveness of MSMEs in Indonesia - Alifia Nasya Manurung; Ramandha Niswan; Tri Deby Damayanti; Fitri Hayati (Journal Informatic, Education and Management (JIEM), 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia’s national economy; however, they continue to face structural challenges, particularly in terms of access to capital, managerial capacity, and business competitiveness. Within the framework of Islamic economics, sharia cooperatives serve as strategic microfinance institutions that not only provide sharia-based financing but also function as agents of economic empowerment. This study aims to analyze and develop a sharia cooperative entrepreneurship model to enhance the performance and competitiveness of MSMEs in Indonesia. This research employs a qualitative descriptive approach using library research and content analysis of relevant academic literature, policy reports, and previous studies. The findings indicate that an integrated sharia cooperative entrepreneurship model—encompassing sharia-based financing, entrepreneurial education, business mentoring, service innovation, digitalization, and collaborative business networks—significantly improves MSME performance in a sustainable manner. Furthermore, sharia cooperative support contributes to strengthening MSME competitiveness by enhancing managerial capabilities, operational efficiency, and market access. Therefore, the development of sharia cooperative entrepreneurship represents an effective institutional strategy to foster inclusive, competitive, and sustainable MSME growth in accordance with Islamic principles.